Brain barriers and brain fluid research in 2016: advances, challenges and controversies. Issue 1 (December 2017) - Keep, Richard; Jones, Hazel; Drewes, Lester
Abstract This editorial highlights some of the advances that occurred in relation to brain barriers and brain fluid research in 2016. It also aims to raise some of the attendant controversies and challenges in such research.